Islamic Eco-Theological as Local Wisdom for The Preservation of Natural Environment - Ibadulloh, Irsyad; Mutaqin, Rizal Samsul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Environmental damage that has become a global problem not only affects people's lives, but also encourages many communities and researchers to find solutions to preserve the natural environment. Indigenous local wisdom is one way that is believed to be able to prevent environmental damage because it is able to respect and live in friendship with nature. This study examined the concept of ecotheology in Pamali as the indigenous people of Kampung Dukuh's local wisdom in preserving the natural environment. This research used a case study method intended to analyse the practice of environmental conservation in Kampung Dukuh based on pamali. Interviews, direct observation, and involved observation were used to collect data for this study. In line with the concept of ecotheology that connects humans, God and nature, pamali as local wisdom of the indigenous people of Kampung Dukuh can simplify and facilitate indigenous people in applying ecotheology as an effort to maintain the balance of life and the preservation of natural environments such as forests.